Resource sharing activities among fisheries libraries under the Ministry of Agriculture in Indonesia a survey with implications towards the development of the Indonesian Fisheries Information System - Sri Wardiningsih R.; Buenrostro, Juan Jr. C.; Maclean, John L. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1988)
This study attempts to survey the status and prospects of existing resource sharing activities among thirteen fisheries libraries under the Ministry of Agriculture in Indonesia, and to recommend ways to improve them to further develop the INFIS network.
The survey was conducted using the questionnaire as a tool for gathering data. The interview method was used to get data from the thirteen fisheries library respondents under the Ministry of Agriculture as members of INFIS, for the purpose of seeking complete information.
The findings show that most of the respondents are involved in cooperative activities i.e. staff training, production of bibliographic tools, union cataloging, production of extension manual and abstracts. None of the INFIS members perceived that theri organizational policies hampered their participation in resource sharing activities.
The communication facility used most frequently by those libraries to inquire for information is the telephone, because of their distant location. All library respondents are serving clientele of other libraries. They also referred the clientele to use other libraries to maximize satisfaction of their information needs.
The librarians agreed that resource sharing activities are the most important aspects for speeding up the information growth under and financial constraint, particularly for speeding up the development of INFIS network. Nevertheless, the training of the library staff also constitutes the most important aspect for accelerating the development of the National Fisheries Information Network. The implication of resource sharing is to support INFIS objectives and its development.
The study recommends that the formal written agreement should be drawn up to specify the responsibilities and benefits of network participation. Whereas cooperative activities such as union cataloging, cooperative acquisitions, and others, should be planned and implemented to minimize duplication of resources. A broader network of fisheries information should be established, with the Directorate General of Fisheries (DGF) as the Coordinating Library; because the DGF under the Ministry of Agriculture is responsible for fisheries administration. The flow and distribution of information would be very smooth because of the good cooperation among fisherires libraries.
Typescript.
Special Problem (Master of Library Science)
Keywords: Fishery libraries -- Indonesia; Library cooperation -- Indonesia